2012
DOI: 10.1038/labinvest.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of telencephalic neural progenitors induced from embryonic stem cells into subacute phase of focal cerebral ischemia

Abstract: Cerebral ischemia causes neuronal death and disruption of neural circuits in the central nervous system. Various neurological disorders caused by cerebral infarction can severely impair quality of life and are potentially fatal. Functional recovery in the chronic stage mainly depends on physical treatment and rehabilitation. We aim to establish cell therapy for cerebral ischemia using embryonic stem (ES) cells, which have self-renewing and pluripotent capacities. We previously reported that the transplanted mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although one group found teratoma formation was independent of pre-differentiation (Erdo et al, 2003), several other groups have found efficacy of pre-differentiated grafts without evidence of tumor formation. ESCs-derived neural progenitor cells (Takagi et al, 2005; Fujimoto et al, 2012; Hayashi et al, 2006), vascular progenitor cells (Oyamada et al, 2008), and mesenchymal stem cells (MSCs) (Liu et al, 2009) have been shown to exert salutary effects after stroke without noticeable tumorigenesis. …”
Section: Cellular Therapies From Different Cell Sourcesmentioning
confidence: 99%
“…Although one group found teratoma formation was independent of pre-differentiation (Erdo et al, 2003), several other groups have found efficacy of pre-differentiated grafts without evidence of tumor formation. ESCs-derived neural progenitor cells (Takagi et al, 2005; Fujimoto et al, 2012; Hayashi et al, 2006), vascular progenitor cells (Oyamada et al, 2008), and mesenchymal stem cells (MSCs) (Liu et al, 2009) have been shown to exert salutary effects after stroke without noticeable tumorigenesis. …”
Section: Cellular Therapies From Different Cell Sourcesmentioning
confidence: 99%
“…35,36 ESCs-derived mesenchymal stem cells, vascular progenitor cells, and neural progenitor cells have been revealed to provide valuable effects without visible tumorigenesis. 37,38 Neuronal progenitor cells derivative from ESCs are capable of decreasing infarct volume, rendering neurogenesis, and improving developmental behavior. 39 Transferred embryonic neural stem cells are able to motivate angiogenic cytokines, through vascular endothelial proliferation within 15 days post cerebral ischemia.…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…Human‐derived ESCs have been broadly investigated during current years for generation of different types of neurons . ESCs‐derived mesenchymal stem cells, vascular progenitor cells, and neural progenitor cells have been revealed to provide valuable effects without visible tumorigenesis . Neuronal progenitor cells derivative from ESCs are capable of decreasing infarct volume, rendering neurogenesis, and improving developmental behavior .…”
Section: Stem Cell‐based Therapiesmentioning
confidence: 99%
“…Previous studies have shown that neural stem/ progenitor cells can protect dying neurons in the central nervous system and preserve vision after injecting into eye. 6,[16][17][18][19] The purpose of this study is to investigate whether hESC-derived NSCs induced by small molecules can preserve vision when injected into the Royal College of Surgeons (RCS) rat, a wellestablished retinal degeneration model. In the RCS rat, the retinal pigment epithelial cell (RPE) fails to phagocytose shed outer segment material due to a mutation in the MertK gene.…”
Section: Introductionmentioning
confidence: 99%